Fingerprinting Cynara scolymus L. (Artichoke) by Means of a Green Statistically Developed HPLC-PAD Method - Souza, Otávio Aguiar [UNESP]; Carneiro, Renato Lajarim; Vieira, Thiago Henrick Martins [UNESP]; Funari, Cristiano Soleo [UNESP]; Rinaldo, Daniel [UNESP] (Springer Nature, 2018)
The process to develop a chromatographic method for fingerprinting complex matrices should be performed through a multiparameter approach that could lead to the desired separation and save environmental resources such as organic solvents and energy. In other words, this process should be pursued by employing an optimized experimental design and having a response function which takes into consideration separation parameters together with environmental parameters. Green Analytical Chemistry principles should be pursued during all steps of the research. This work presents a heuristic approach to develop a high-performance liquid chromatography method for fingerprinting an extract from leaves of Cynara scolymus L., a food plant consumed worldwide. A fractional factorial design was used to identify relevant chromatographic variables followed by a comprehensive design for optimization purposes (Doehlert design). A response function called green chromatographic fingerprinting response was employed to obtain a compromise between fingerprint quality and low environmental impact of the method. This optimized approach led to the development of a robust and green method for fingerprinting C. scolymus by HPLC-PAD. This method proved to be greener than the reference method reported in literature and compatible even with no state of art HPLC instruments because the system backpressure did not exceed 15 MPa and the column temperature was 35 °C.
Keywords: Doehlert; Experimental design; Green analytical chemistry; Green liquid chromatography; Metabolic fingerprinting; Optimization